Social Media & Music Videos: Ethics Impact on Grade 6 Students: Dampak Aplikasi Jaringan Sosial dan Platform Video Musik terhadap Etika Komunikasi Siswa SD Kelas 6 - Rizky Alfiyah Arifin; Mahardika Darmawan Kusuma Wardana (Academia Open, 2023)
The purpose of this study was to determine the impact of the tik-tok application on students' communication ethics in an elementary school located in Sidoarjo Regency. The approach used in this research is qualitative with the type of case study research. The subjects in this study were high school students at SDN Kalisampurno 1 Tanggulangin. Based on the results of the study, it was concluded that the use of the tik-tok application had a positive impact on students being more daring to admit when they made mistakes and being responsible, and excessive ones could have a negative impact on students' communication ethics. This can be seen from the results of research which shows that there are still many students who do not meet the indicators of good communication ethics in behaving in school. Highlights: The study examines the impact of the TikTok application on communication ethics of elementary school students in Sidoarjo Regency. The research follows a qualitative approach, specifically a case study design. Findings suggest that TikTok has both positive and negative effects on students' communication ethics, with some students demonstrating good ethics while others fall short. Keywords: TikTok application, Communication ethics, Elementary school students, Sidoarjo Regency, Qualitative research